Домашние животные: Собаки .Кошки. Лошади. Коровы - Дмитриев Юрий Дмитриевич (Соседи по планете, 1997)
6-11 Экземпляры: ф. 23 (20210818) / Инвентарный номер: 29760 / Цена: 25.00 / Авт.знак: Д 53 / ББК: 28.693.36